2012
DOI: 10.1021/ie300595e
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Thermal Hazards of Tributyl Phosphate with Nitric Acid

Abstract: The accelerating rate calorimetry studies on the tributyl phosphate and nitric acid reactions at various acid concentrations revealed that the conditions for red oil formation may vary with acid strength. The accelerating rate calorimeter studies supplemented with FT-IR characterization of the end products confirmed the formation of red oil at temperatures as low as 75 °C. This study thus strongly advocates for a revisit of safety limits set in the fuel reprocessing plants to prevent red oil formation. The che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…• the reactions of red oil formation and red oil decomposition have to be clearly distinguished. • the conditions under which the red oil formation occurs have to be studied further with care and any combination that reports a lower onset temperature (such as those reported by Smitha et al (23,24), Glossop (34), and Chandran et al (35)) than the well quoted safety margin of 403 K (130 • C) should be taken seriously and never ignored. • The effect of radiolysis of the organic phase and accumulation of the radiolytic degradation products in the aqueous phase may have an accelerating effect on red oil formation and also on the decomposition behavior and have to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• the reactions of red oil formation and red oil decomposition have to be clearly distinguished. • the conditions under which the red oil formation occurs have to be studied further with care and any combination that reports a lower onset temperature (such as those reported by Smitha et al (23,24), Glossop (34), and Chandran et al (35)) than the well quoted safety margin of 403 K (130 • C) should be taken seriously and never ignored. • The effect of radiolysis of the organic phase and accumulation of the radiolytic degradation products in the aqueous phase may have an accelerating effect on red oil formation and also on the decomposition behavior and have to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Smitha et al (23,24) studied the thermal behavior of neat TBP under adiabatic conditions employing ARC and observed multiple exothermic activities in the temperature range 523-698K (250-425 • C). The results showed exothermic excursions, respectively at 524, 653, and 703 K (251, 380, and 430 • C) with enthalpy values of 128.2, 1348.7, and 581.8 J g −1 .…”
Section: Studies and Reviews On Red Oilmentioning
confidence: 99%
“…It has been reported in our earlier work that the reason for the exothermic behavior of TBP with nitric acid is due to the oxidation of butanol to butanoic acid. 8 The butanol is formed from the hydrolysis of TBP in the presence of H 2 O and HNO 3 . Nitric acid acted as an oxidizing agent.…”
Section: Resultsmentioning
confidence: 99%
“…The vigor of the reaction is proportional to the strength of the acid. 8 Here, the influence of various diluents on the oxidative reaction between TBP and nitric acid system is analyzed using various analytical techniques such as FTIR, NMR, and GC-MS. The biphasic residue after reaction was separated into aqueous and organic phases, and appropriate solvents were used to dissolve them for characterization purposes.…”
Section: Resultsmentioning
confidence: 99%
“…erefore, researchers studied the degradation of TBP or the thermal reaction between TBP and nitric acid. Smitha et al reported the reaction of TBP with nitric acid at different acid concentrations [12][13][14][15]; the influences of diluents on the reactions and the behaviors of heat emission were also studied previously [5,[16][17][18][19][20][21][22][23]. Nazin et al reported thermal explosions in mixtures of TBP with nitric acid [14,24].…”
Section: Introductionmentioning
confidence: 99%